Quantitative Antibiotic Use Profile in Typhoid - Hidayatul Kurniawati; Marianti (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Background. Typhoid fever is a common health problem in developing countries. Antibiotics are used to treat typhoid fever which is caused by a bacterial infection. Selection and use of appropriate and rational antibiotic therapy can determine a success in treatment to avoid bacterial resistance and minimize drug side effects. This study aims to determine the rationality of the use of antibiotics in adult patients diagnosed with typhoid fever in the Inpatient Installation of X Hospital in Yogyakarta. Method. Non-experimental research with descriptive observational research design and retrospective data collection. The sample of this study was inpatients with a diagnosis of typhoid fever and was recorded at the X Hospital Medical Records Installation in Yogyakarta for the period January 2016 - December 2017 which was included in the inclusion criteria. Result. Data taken came from 75 medical records that were included in the inclusion criteria. Patients were dominated by female patients as many as 64% and the adult age range was 18-30 years. The single most widely used antibiotic was levofloxacin in 27 cases (36%). The use of antibiotics with the right indication was 75 patients (100%), the right type was 75 patients (100%), the exact duration of administration was 64 patients (85.33%), the right dose was 73 patients (97.33%), the right interval was 73 patients (97.33%) and the right route of administration were 75 patients (100%). Conclusion. The rationality of using antibiotics is good with accuracy> 75%.